Caracterização química, microbiológica e toxicidade do Iodo de esgoto da estação Mangueira, Pernambuco, Brasil - Santos, Ednaldo Ramos dos (2011)
The final disposal of sewage sludge generated in sewage treatment plants has been a challenge for environmental, chemical and economical processes. The aim of this work was the chemical characterization for the content of total phenol and carbon, heavy metals, as well as the presence of filamentous bacteria and fungi in sewage sludge at the station of Mangueira, Pernambuco, Brazil. Furthermore, investigated the production of proliphenoloxidase as an important attribute for the removal of phenolic compounds in soil, as well as the toxicity of the sludge with Artemia salina. The results obtained with microbiological characterization indicated the presence of total coliforms and the absence of fecal coliforms. In relation to isolated filamentous fungi, we observed the presence of Penicillium sp., Chrysosporium sp., Scedosporium sp., Monotospora sp. and Aspergillus sp. Analyses performed with the 24 filamentous fungi cultures indicated that seven strains of Chrysosporium sp., two of Scedosporium sp., one of Monotospora sp. and one of Penicillium sp. were producing phenoloxidase enzyme and, thus, they were capable of degrading phenolic compounds. The chemical characterization of sewage sludge indicated a total carbon content of sludge 14.7833mg/100mg, while total phenols showed the value of 0.198 mg/L, demonstrating that both chemical components showed a low concentration. The heavy metals found in the sludge were as follows: Ca, Mg, Al, Zn, Cu, Ni, Cd, Fe and Cr, demonstrating that the levels are consistent with the law of CONAMA, Resolution No. 375/2006, except for Mn. The toxicity tests performed with the dried sewage sludge, using the Artemia salina bioassay, showed that, once the sludge reaching water bodies, the lethal concentration was 32.44%. Therefore, studies with sewage sludge of the station Mangueira indicated that the majority of metals does not have characteristics of metals polluting the soil when sewage is used in agriculture. Thus, it can be an economically viable and environmentally safe, once treated properly